Asbestos waste audit and recycling in an automobile brake manufacturing facility - Agamuthu, Pariatamby; Mahalingam, R.; Chan, Y.M. (2000)
A waste audit study, using a modified protocol based on the U.S. EPA Waste Audit Guidelines, was carried out in a brake manufacturing facility, by observing and analyzing each of the process steps-mixing, preforming, molding, oven curing, cutting, grinding, drilling, wear evaluation, chamfering, and branding and packaging. Additionally, studies on waste minimization through recycling of the waste brake lining dust into the virgin mix and the effect of this recycling on subsequent product performance quality were also carried out. The audit showed that there was generation of waste at just about every step of the process, as evidenced by weight loss calculations on the original mix entering the process. For example, in the cutting step this loss was about 30 percent, in grinding it ranged from 10.64 percent to 13.03 percent, in drilling from 2.17 percent to 6.8 percent, and in chamfering from 0.49 percent to 1.07 percent; in the case of cutting this included both cutting residues and fines while in the rest of the cases these were only fines. Next, in evaluating the recycling of the fines, recycling 5 percent to 10 percent of the lining waste dust into the virgin mix retained the specific gravity of the brake lining samples well within the specification requirement range of 2.12 to 2.32. Additionally, inertia dynamometer tests were carried out on the linings produced from the 5 percent and 10 percent recycling mix, with the virgin mix as the control. The performance characteristics studied were effectiveness, fade, post-burnish effectiveness, post-fade effectiveness, and speed spread. Both the 5 percent and 10 percent recycled ones performed as good as the control one, although the S percent one exhibited lower green effectiveness and greater speed spread. Finally, based on an analysis of waste management and disposal costs, and in order also to minimize waste generation, a few simple process changes are suggested.